PENCAHAYAAN DENGAN PERSENTASE PENUTUPAN DINDING AKUARIUM YANG BERBEDA UNTUK DAYA TETAS DAN KELANGSUNGAN HIDUP LARVA IKAN KELABAU (Osteochilusmelanopleura Blkr) - Rahmadani Rahmadani; Rukmini Rukmini; Pahmi Ansyari (Fish Scientiae, 2019)
This research to know influence of illumination with percentage closing of different aquarium wall to energy hatch and continuity of baby fish life of kelabau (Osteochilus melanopleura Blkr) and also know different of chemical value and physics at each treatment. Result of research indicate that treatment of C (hatch of egg of kelabau at glasswall aquarium 100% closed) refresenting best treatment because showing energy average hatch egg (%) fish of kelabau biggest with value 63,80% compared to treatment of A (hatch of egg of kelabau at glass wall aquarium 100% open) with value 50,47% and treatment of B (hatch of egg of kelabau at glass wall aquarium 50% closed) with value 54,66%. At result of this research, continuity of fish baby life of kelabau best is treatmentof B (conservancy of baby fish of kelabau at glass wall aquarium 50% closed) that isequal to 71,90%. Compared to the continuity of goldfish baby life at Tables 9, got the continuity of best life at treatment of B (temperature 28°C) that is egual to 65,33%. Result of this research prove that temperature irrigate different aquarium very having an effecton to continuity of fish baby life of kelabau. Temperature irrigate aquarium at treatment B (conservancy of baby fish 50% closed) is 26,5°C that is still in a good temperature gyration to the continuity of baby fish of kelabau.